Comparing patterns of human harvest and predation by Eurasian lynx Lynx lynx on European roe deer Capreolus capreolus in a temperate forest - Krofel, Miha; Jerina, Klemen; Kljun, Franc; Kos, Ivan; Potočnik, Hubert; Ražen, Nina; Zor, Petra; Žagar, Anamarija (European Journal of Wildlife Research, 2017)
Human harvest is the most important mortality factor for wild ungulates in Europe and can affect several aspects of ungulate biology. There is a growing concern about possible negative side-effects of human harvest. To better understand differences between human and natural mortality we compared the extent, age and sex structure, nutritional condition, spatial and temporal distribution of human harvest and natural predation by the Eurasian lynx Lynx lynx on the European roe deer Capreolus capreolus, the most abundant wild ungulate in Europe. Compared to the human harvest, lynx were less likely to kill fawns and yearlings than adults, and among adult deer lynx were more likely to kill females. Proportion of roe deer with fat-depleted bone marrow was higher among lynx prey than among harvested animals. Average lynx kill rate was estimated to 47.8 roe deer / year and lynx predation was considerably lower than the human harvest in the same area. While human harvest increased with higher roe deer density, lynx predation was similar across the gradient of roe deer densities. Comparison with other countries indicated that differences between human harvest and natural mortality of ungulates vary considerably in different parts of Europe. Variation in hunting practices and, even more importantly, carnivore predation may have an important role in buffering unwanted side-effects of harvest of wild ungulates.